2000
DOI: 10.1002/etc.5620190224
|View full text |Cite
|
Sign up to set email alerts
|

Toxic responses of medaka, D‐rR strain, to polychlorinatednaphthalene mixtures after embryonic exposure by in ovo nanoinjection: A partial life‐cycle assessment

Abstract: Polychlorinated naphthalenes (PCNs) are organic compounds with some chemical properties and uses similar to polychlo‐rinated biphenyls. Polychlorinated naphthalenes have been detected in biota from certain aquatic environments. The toxicities of several PCN technical mixtures (Halowax) to medaka (Oryzias latipes) were determined by use of an embryo nanoinjection method. Medaka eggs (early gastrula) were injected with 0.5 nl of triolein (vehicle control) or 0.5 nl of four to five graded doses (0.3–30 ng/egg) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…For example, Engwall et al (17) observed EROD induction and lethality in chicken embryos with exposure to a mixture of 1,2,3,4,6,7/1,2,3,5,6,7-hexa-CNs 66 and 67 (ED 50 for EROD induction ) 0.06 mg/kg of egg), but when they tested 1,2,3,4,5,6,7-hepta-CN (PCN 73), they observed less EROD induction (the greatest dose, 3 mg/kg, caused only 50% of the maximal induction caused by the hexa-CN mix). Similarly, REPs of Halowax mixtures determined in H4IIE-luc cells (Halowax 1051 > 1014 > 1013) were different from REPs determined in medaka fish (Halowax 1014 > 1013 > 1051) (48). Interestingly, the relative rank order potency of CYPIA expression in rainbow trout sac fry is consistent with our results with the order being 66/67 > 73 > Halowax 1014 (21).…”
Section: Discussionsupporting
confidence: 88%
“…For example, Engwall et al (17) observed EROD induction and lethality in chicken embryos with exposure to a mixture of 1,2,3,4,6,7/1,2,3,5,6,7-hexa-CNs 66 and 67 (ED 50 for EROD induction ) 0.06 mg/kg of egg), but when they tested 1,2,3,4,5,6,7-hepta-CN (PCN 73), they observed less EROD induction (the greatest dose, 3 mg/kg, caused only 50% of the maximal induction caused by the hexa-CN mix). Similarly, REPs of Halowax mixtures determined in H4IIE-luc cells (Halowax 1051 > 1014 > 1013) were different from REPs determined in medaka fish (Halowax 1014 > 1013 > 1051) (48). Interestingly, the relative rank order potency of CYPIA expression in rainbow trout sac fry is consistent with our results with the order being 66/67 > 73 > Halowax 1014 (21).…”
Section: Discussionsupporting
confidence: 88%
“…This is also the time for the formation of livers in the embryos. 25 For Fenton and electro-Fenton effluents, the number of embryo lesions was signicantly higher than that in the controls and MBR effluent (p < 0.05) (Table 3). No embryo could be hatched in MBR-F and MBR-EF effluents of dilutions more than 25%.…”
Section: Short-time Chronic Toxicitymentioning
confidence: 92%
“…At sampling day, three random larvae per tank (N = 36 per treatment, 24 for the 14 days exposure) were photographed for morphometric analyses: larvae length and yolk sac area were measured later using the ImageJ software (Rueden et al, 2017). All larvae were monitored for signs of BSD (pericardial and yolk sac edemas, hemorrhages, craniofacial and spinal deformities) and a severity index ranging from 0 to 1 was calculated for each tank according to the scoring scheme of Villalobos et al (2000) with the modifications from Scott and Hodson (2008). Larvae were then quickly and carefully dissected under the microscope: the heart of each larva was separated from the rest of the body using fine forceps (Dumont #5, Fine Science Tools, Heidelberg, Germany).…”
Section: Experimental Designmentioning
confidence: 99%